Oracle weblogic server 12c administration handbook - Alapati, Sam R; Ohio Library and Information Network (New York : McGraw-Hill Education, 2014)
Through expert instruction and real-world examples, this book fully explains the latest management tools and techniques for maintaining a high-performance enterprise application framework. Learn how to work from the Oracle WebLogic Server Administration Console or command line, configure servers and clusters, deploy applications, and optimize application performance. Tuning, troubleshooting, and load balancing are thoroughly covered in this Oracle Press guide. Topics covered include: installing Oracle WebLogic Server 12c or performing an upgrade; managing domains, server instances, networks, and virtual hosts; working with the WebLogic Scripting Tool feature and Node Manager; building custom network channels and resource adapters; monitoring performance with the WebLogic Diagnostics Framework feature; prioritizing requests using Oracle WebLogic Server Work Managers; configuring Oracle WebLogic clusters and migrating servers and services; deploying Web applications, Enterprise JavaBeans, and Java EE modules; establishing security realms and authenticate and authorize users; and allocating memory, optimizing throughput, and tuning the Java Virtual Machine
10 WebLogic Server Performance Tuning
Keywords: Client/server computing; Web servers